The Effect of Service Quality, Product Quality, Promotion and Price on the Purchase Decision of Motorcycles in the Indah Sakti Showroom - Ahmad Rizky Harahap; Yuniman Zebua; Muhammad Ali Al Ihsan (Quantitative Economics and Management Studies, 2023)
Business in the automotive sector continues to experience the times. Every producer in this field makes innovations that can fulfill consumer desires. It is very important for manufacturers to know the factors driving consumers in making decisions to buy products. In this case, researchers conducted research on consumers of a motorcycle showroom in the city of Rantauprapat. Researchers want to examine the effect of service quality, product quality, promotion and price on the decision to purchase a motorcycle at the Indah Sakti showroom. This study involved 100 consumers who had purchased a motorcycle at the Indah Sakti showroom as respondents. This study used a quantitative approach with data collection methods using a questionnaire instrument which was distributed via WhatsApp and then respondents filled out the questionnaire using the Google form. The results showed that service quality had a significant effect on the decision to purchase a motorcycle at Indah Sakti, product quality had a significant effect on the decision to purchase a motorcycle at Indah Sakti, promotion had a significant effect on the decision to purchase a motorcycle at Indah Sakti and price had a significant effect on the decision to purchase a motorcycle. at Beautiful Sakti.